2018
DOI: 10.1021/acs.langmuir.8b00337
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Attachment of Bimetal Combinations of Transition-Metal Ions to the Surface of TiO2 Nanorods

Abstract: We report the sequential, quantitative loading of transition-metal ions (Cr, Mn, Fe, Co, Ni, and Cu) onto the surface of rod-shaped anatase TiO nanocrystals in bimetallic combinations ( C = 15) to form M,M'-TiO nanocrystals. The materials were characterized with transmission electron microscopy (TEM), powder X-ray diffraction (XRD), elemental analysis, X-ray photoelectron spectroscopy (XPS), and UV-visible spectroscopy. TEM and XRD data indicate that the sequential adsorption of metal ions occurs with the rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…In our previous XPS studies of Co (surface) -TiO 2 and M,M 0 (surface) -TiO 2 we observed Co 2p 3/2 binding energies of 780.5-780.9 eV. 37,43 Based on the new XPS data, it is apparent that the Co 2p 3/2 binding energy for Co (doped) -TiO 2 is approximately 1 eV larger than for Co (surface) -TiO 2 . Choudhury et al report binding energies of 781.4 eV and 797.2 eV for Co 2p 3/2 and 2p 1/2 electrons from XPS study of Co 2+ doped TiO 2 nanoparticles.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 71%
See 1 more Smart Citation
“…In our previous XPS studies of Co (surface) -TiO 2 and M,M 0 (surface) -TiO 2 we observed Co 2p 3/2 binding energies of 780.5-780.9 eV. 37,43 Based on the new XPS data, it is apparent that the Co 2p 3/2 binding energy for Co (doped) -TiO 2 is approximately 1 eV larger than for Co (surface) -TiO 2 . Choudhury et al report binding energies of 781.4 eV and 797.2 eV for Co 2p 3/2 and 2p 1/2 electrons from XPS study of Co 2+ doped TiO 2 nanoparticles.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 71%
“…In previous work, we established a robust protocol for the adsorption of metal ions onto the surface of TiO 2 nanorods as a synthesis method. 34,36,37 The reaction is self-limiting based on the number of surface titanium atoms on the nanocrystal. In the example of Co 2+ adsorbed onto the surface of TiO 2 we observe nearly quantitative uptake of Co 2+ for Co : Ti mass ratio below $0.12, and above this ratio there is no additional uptake.…”
Section: Resultsmentioning
confidence: 99%
“… 71 After that, some scholars used aluminum (Al), iron (Fe), gold (Au) and silver (Ag) as doped ions. 72 However, the photocatalytic activity is related to the relative position of the doped metal ions, which puts forward strict requirements for the selection of metal ions and the preparation process for material doping. Liu et al 73 further clarified the similarities and differences in the reaction mechanism of metal and non-metal ion doping.…”
Section: Effect Of Physical Fields On Photocatalytic Efficiencymentioning
confidence: 99%